Déjà vu with a twist: transglutaminases in bioenergetics and transcriptional dysfunction in Huntington's disease - Kazemi-Esfarjani, Parsa (WILEY-VCH Verlag, 2010)
The article by McConoughey et al in the current issue of EMBO Molecular Medicine examines the contribution of transglutaminase 2 (TG2) to Huntington's disease (HD) pathogenesis. The authors find that TG2 inhibition can ameliorate HD neurodegeneration, and thereby elevate the status of transglutaminases (TGs) to a major therapeutic target—not because of their well-known activity in mutant protein aggregation, but instead based upon their ability to epigenetically modulate transcription and energy production. While the reintroduction of TG inhibition as a therapy for HD may evoke feelings of déjà vu, the outcome this time around could go in a dramatically different direction.